The Influence Of The Working Shift Work And Stress On The Performance Of The Employes - Otfiyantoa Otfiyantoa; Abid Muhtarom; Haris bashory ismail; Henny mahmudah (Universitas Muhammadiyah Metro, 2018)
The progress of an organization will not remove from the existence and the influence of human resources that contained. Efforts to improve the performance of the employees including the attention to shift work and stress the work on the employees. This research aims to find out the influence of partially or simultaneous as well as the most dominant variable about shift work and stress on the performance of the work of the employees employees in PT Jaya Brik Indonesia kemantren paciran lamongan.The research method used in this research is a quantitative method. Samples taken from the research as much as 75 respondents. Techniques data in this research using the questioner and the recording of the document and then in the analysis using multiple linear regression analysis with the help of the program SPSS 24 and eviews 9.The results of the study showed,(1) Shif influential work positive and significant (t count 2,549>1,666 t table) to the performance of employees and work stress have positive and significant (t count 3,294> 1,666 t)table on the performance of the employees (2) Shift work and stress the work simultaneously have positive and significant (f count 10,867 > 1.73 f table) to the performance of employees. (3) the variables most affect the performance of the employees are working shift.Key Words : The Performance of employees, work Shift and Work stress.